1970
DOI: 10.1037/h0028955
|View full text |Cite
|
Sign up to set email alerts
|

Effects of withheld reinforcement on timing behavior of rats with limbic lesions.

Abstract: Animals with septal or cingulate lesions were tested on an 8-sec. or .6-sec. differential reinforcement of low rate schedule of reinforcement. Results showed that timing efficiency of animals with septal lesions was reduced below control levels when they were required to suppress responding for 1.2 sec. or longer. When reinforcements were periodically withheld follow-, ing a correct timing response, rates for all subjects accelerated. The increase in rate was greatest for the animals with septal lesions when t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

1972
1972
1981
1981

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…It is also unlikely that reinforcement density or baseline response rates affect the appearance of the enhanced frustration effect in septal-lesioned animals, since brain-damaged and control animals did not differ in behavioral contrast in either Experiment I or Experiment II. A factor that might account for the disparity between the results of Caplan (1970) and those of Mabry and Peeler ( 1972) and the present experiment is the temporal relationship between omission of reinforcement and the response measure. In the Caplan study, measures of response output occurred immediately after nonreinforcement.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…It is also unlikely that reinforcement density or baseline response rates affect the appearance of the enhanced frustration effect in septal-lesioned animals, since brain-damaged and control animals did not differ in behavioral contrast in either Experiment I or Experiment II. A factor that might account for the disparity between the results of Caplan (1970) and those of Mabry and Peeler ( 1972) and the present experiment is the temporal relationship between omission of reinforcement and the response measure. In the Caplan study, measures of response output occurred immediately after nonreinforcement.…”
Section: Discussionmentioning
confidence: 98%
“…It has generally been found that onusslon of reinforcement is followed by accelerated responding or increased perseveration in the septal-Iesioned animal above control levels. Caplan (1970) found, for example, that when scheduled reinforcement was omitted on a DRL schedule all subjects accelerated their response rates, but the increase was greatest for septal-Iesioned animals. Mabry and Peeler (1972) found, however, that animals with septal lesions and control animals did not differ in response to frustrative nonreward in a double-runway task.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Changing the temporal criterion for the reinforcement of a response also changes the duration by which the availability of reinforcement is delayed after a nonreinforced response. For example, although the latter contingency has been said to be aversive (Caplan, 1970;Hearst, Koresko, and Poppen, 1964) there is no direct evidence to show this. Similarly, while reinforcement probably functions as a discriminative event in determining the duration of the next IRT (e.g., Farmer and Schoenfeld, 1964;Weiss, Laties, Siegel, and Goldstein, 1966), this has not been shown directly because the temporal contingency is the same after reinforcement and after nonreinforced responses.…”
mentioning
confidence: 99%
“…In order to directly compare the performance of the three groups , efficiency ratios for each group for the last five sessions were computed. This ratio has been defined as the ratio between the number of reinforced responses and the total number of responses (Caplan, 1970). It varies from 0 to 1.0, with 1.0 representing optimal response efficiencies.…”
Section: Resultsmentioning
confidence: 99%